Engineering students involved with printing business on campus - Siti Nurfarmy, Ibrahim (2020)
Recognizing the interest of university students in sports apparel, this kind of idea gave the idea of Civil Engineering Technology student, Pan Chuan Sin, 24, a venture into the field of sports apparel printing business.